Flexural behavior of Expanded Polystyrene core Reinforced Concrete Sandwich Panels with different construction methods and end conditions. (December 2021) - Ahmad, Adil; Singh, Yogendra
Graphical abstract: Highlights: Efficacy of EPS core sandwich panels in out-of-plane flexure is examined. Effect of boundary conditions on strength and ductility is studied. Effect of sprayed and poured concrete method of construction is investigated. Effect of orientation of corrugations in EPS panel is studied. Abstract: The effect of construction methods and end conditions on flexural behavior of Expanded Polystyrene (EPS) Core Reinforced Concrete Sandwich Panels (RCSP) under out-of-plane flexure loading is studied, experimentally. Total 21 specimens are constructed using factory made corrugated EPS panels and wire mesh. The specimens are constructed using different construction (pouring and spraying of concrete) methods, with varying combinations of wythe thicknesses, boundary conditions (presence and detailing of RC beams along the supported edges), and alignment of corrugations in the EPS core. Specimens are tested under four-point bending, with simply supported condition, in displacement control mode. The influence of the considered parameters on cracking pattern, failure mode, strength, moment-rotation curve and ductility are studied. The failure mode of the EPS core RCSP specimens is mainly governed by the edge condition at supports, whereas, the method of construction and thickness of wythes do not have much influence of the failure mode. The thickness and construction method of the wythes has significant effect on the initial behaviour of panels up to cracking, but has only limited effect on the ultimate load capacity, as it mainly resisted by the wire-mesh reinforcement in primarily catenary action, in most of the tested specimens.